1998
DOI: 10.1210/jcem.83.7.4950
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Luteal “Rescue” on the Expression and Localization of Matrix Metalloproteinases and Their Tissue Inhibitors in the Human Corpus Luteum

Abstract: Luteolysis is associated with tissue remodeling probably involving the matrix metalloproteinases (MMPs) and their specific tissue inhibitors (TIMPs). This study investigated the expression and localization of the major MMPs and TIMPs in the human corpus luteum throughout the luteal phase and after luteal rescue with hCG. Corpora lutea (n = 9) were collected at hysterectomy and were dated by serial urinary LH estimation. In addition, corpora lutea (n = 3) were collected from women who had received daily doublin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…For example, MMP-9 activity peaks in both early and late luteal phases and MMP-2 activity is maximal in the late corpus luteum, when vessels are regressing (Duncan et al, 1998). A similar observation was made in the endometrium, in which MMPs are overexpressed during the late menstrual phase, when hemorrhage occurs as a result of vessel breakdown (Salamonsen, 1994).…”
Section: Matrix Metalloproteinases and Vascularsupporting
confidence: 56%
See 1 more Smart Citation
“…For example, MMP-9 activity peaks in both early and late luteal phases and MMP-2 activity is maximal in the late corpus luteum, when vessels are regressing (Duncan et al, 1998). A similar observation was made in the endometrium, in which MMPs are overexpressed during the late menstrual phase, when hemorrhage occurs as a result of vessel breakdown (Salamonsen, 1994).…”
Section: Matrix Metalloproteinases and Vascularsupporting
confidence: 56%
“…Recent studies have shown that MMPs are overexpressed not only during angiogenesis, but also during the involution and/or breakdown of vascularized organs such as the corpus luteum, the endometrium, and the mammary gland (Ambili et al, 1998;Duncan et al, 1998;Salamonsen, 1994). These findings suggest that proteolytic enzymes may play an important role not only in the initial phases of angiogenesis, but also in the later stages of this process when microvessels no longer proliferate and are gradually reabsorbed.…”
mentioning
confidence: 99%
“…In addition, archival corpora lutea that had been immediately frozen and stored at K70 8C from previous studies (Duncan et al 2005b were also available. Frozen tissue quarters for mRNA extraction were available from three early luteal, seven mid-luteal, six late luteal and five corpora lutea that had been 'rescued' (women were given daily doubling doses of exogenous hCG (Serono Laboratories, Welwyn Garden City, UK), starting at 125 IU, from LHC7 for 5-8 days until surgery) as described previously (Duncan et al 1996(Duncan et al , 1998b.…”
Section: Collection Of Human Ovarian Tissue and Human Corpora Luteamentioning
confidence: 99%
“…In simulated early pregnancy, human chorionic gonadotrophin (hCG) has effects on immune cells, endothelial cells and fibroblasts (Duncan et al 1998a, 1998b, Duncan 2000, Wulff et al 2001) which do not express LH/hCG receptors (LHCGR). Therefore, if paracrine molecules, which are regulated by hCG, are involved in luteolysis, these molecules should be the products of steroidogenic cells and have receptors on target cells.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular events involved in luteolysis and how they are prevented by exposure to human chorionic gonadotrophin (hCG) remain unclear (Behrman et al 1993, Duncan 2000. As hCG has effects on macrophages (Duncan et al 1998a), fibroblasts (Duncan et al 1998b) and blood vessels (Wulff et al 2001), that do not express luteinising hormone (LH)/hCG receptors, paracrine molecules must have important roles in luteal function (Duncan 2000).…”
Section: Introductionmentioning
confidence: 99%